Navigating crisis: COVID 19’s impact on Entrepreneurship in Morocco - Benchrifa, Hanaa; Karima, Lakhdar (Journal of Entrepreneurship, Business and Economics, 2024)
This article investigates the repercussions of the COVID 19 pandemic on entrepreneurship in Morocco, utilizing bibliographic research approach drawing from Google Scholar and IMIST database. It delves into governmental and non-governmental studies, elucidating the adverse impacts on various economic sectors while advocating for enhanced innovation and the production of high value goods. Furthermore, it examines Morocco’s proactive measures in response to the pandemic. Additionally, the study explores strategies outlined in the new development model to alleviate crisis and stimulate economic revival including fostering social and female entrepreneurship and extending social protection to auto-entrepreneurs. This research stand out for its focused analysis on Morocco’s context and the scrutiny of specific pandemic response measures. Its findings carry significant implications for informing policy decisions and actions at reinforcing entrepreneurship and economic resurgence not only in Morocco but also in similar contexts globally. Literature Review Keywords: COVID 19 Pandemic; Entrepreneurship; Morocco; Economic Effects; Crisis Responses Reference to this paper should be made as follows: Benchrifa, H., & Karima, L. (2023). Navigating crisis: COVID 19’s impact on Entrepreneurship in Morocco. Journal of Entrepreneurship, Business and Economics , 11 (2), 245–274.